Membangkitkan Kembali Fitrah Keayahan dalam Perspektif Islam: Jalan Efektif Mencegah Perselingkuhan: Reawakening Fatherhood in Islamic Perspectice: An Effective Way to Prevent Infidelity - Azwar, Azwar (Litera Academica Publishing, 2025)
Infidelity in marriage is a serious issue that can damage family harmony and negatively impact the well-being of individuals and society. This study aims to analyze the causes behind the increasing cases of infidelity in Indonesia, as well as the role of fatherhood in preventing it. The research employs a literature review method with a qualitative descriptive approach, covering psychological, sociological, and religious theories regarding family and the role of fathers. The findings of this study indicate that infidelity is often triggered by poor communication within the household, an inability to fulfill the role of a husband, and the influence of social media, which opens opportunities for relationships outside of marriage. The concept of fatherhood, emphasizing the father’s role as a leader, protector, and educator within the family, proves to strengthen family structure and prevent infidelity. This research recommends the strengthening of family education, fostering the role of fathers, and closer supervision of technology use in marital relationships. The findings have important implications for educational institutions, society, and the government in developing programs that can reinforce family values and reduce the incidence of infidelity.